Una especie de áfido toxicogénico observada en cacao (Theobroma cacao L. - Salas, A.; Hansen, J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Irregular discolored zones, leaf corrugation and occasional leaf drop were observed in seedling and adult plants of cacao in Turrialba. The aphid Neomyzus circumflexus was found to be consistently associated with this damage to young leaves. Identical symptons were induced by caging the aphid on young healthy cacao leaves; the symptoms persisted on old leaves after the aphids had disappeared, but new aphid-free shoots from affected branches were healthy. The discoloration, corrugation and accasional leaf drop are considered to be due to the toxicogenic effect of the aphid.